Miejsce systemu informacyjnego w strategii współczesnego przedsiębiorstwa - Szplit, Andrzej; Szplit, Marcin (The role of the information system in the strategy of a contemporary enterprise, 2005)
The article defines the role of the information system in the strategy of an enterprise. It has a huge influence on effectiveness of knowledge management and the possibility to create a self learning or intelligent business.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 458-462